MEMAKNAI KERAGAMAN: The Others dalam Konstruksi Sosial Para Elit Kelompok-kelompok Keagamaan di Kota Mataram - Umam, Fawaizul (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2016)
Based on the urgency of the involvement of the groupsâ€™ views on the others in any peace initiation, this study attempted (1) to investigate how the leaders of religious groups in Mataram socially constructed the others and (2) to determine the typology of their social constructions by relying on three main paradigms of religiosity (exclusivism, inclusivism, pluralism). The leaders of religious groups were chosen as a major subject because they had contributed significantly to the social dynamics of the Muslims in this city; as religious elites (ulama), they were not only cultural brokers, but also active creators of social change. To analyze their social constructions on the others, this research used the Bergerâ€™s social constructionism theory. Their social constructions excavated from purposively selected informants, namely the formal or informal elites of religious groups like the Ahmadiyya, Salafists, Tablighi Jamaat, Shiite, and the traditionalist (Nahdlatul Wathan) and modernist (Muhammadiyah) Islamic groups. It was concluded that their social constructions actually emerged through three moments of dialectic which formed the subjective and objective realities on the others. Through those social constructions, they defined the others. All of their social constructions typologically tended to be exclusive, in certain limits also inclusive, and pluralistic tendencies tended to be absent. Based on the typefication, this study proposed a number of ideal solutions for creating the coexistence of Islamic religious groups in Mataram..Bertolak dari urgensi pelibatan pandangan masing-masing kelompok tentang the others dalam setiap inisiasi perdamaian, studi ini mengkaji (1) konstruksi sosial para elit kelompok-kelompok keagamaan di Kota Mataram tentang the others sekaligus menentukan (2) tipologinya berdasar tiga model utama keberagamaan, yakni eksklusivisme, inklusivisme, dan pluralisme. Para elit dipilih sebagai subjek karena mereka berperan signifikan dalam kelompok masing-masing. Dalam dinamika sosial masyarakat Muslim Kota Mataram, mereka kurang-lebih adalah ulama yang berperan sebagai â€œmakelar budayaâ€ sekaligus kreator aktif perubahan sosial. Untuk memahami konstruksi sosial para elit tentang the others, studi ini menerapkan teori konstruksi sosial Berger. Data utama digali dari para informan yang dipilih secara purposif, yakni mereka yang secara formal maupun informal memimpin kelompok-kelompok keagamaan Islam seperti Ahmadiyah, Salafi, Jamaâ€™ah Tabligh, Syiâ€™ah, dan juga kelompok tradisionalis (Nahdlatul Wathan) dan modernis (Muhammadiyah). Hasil kajian menunjukkan bahwa konstruksi sosial mereka muncul lewat tiga momen dialektik yang membentuk realitas subjektif sekaligus objektif tentang the others. Hal itu menentukan cara mereka selaku elit kelompok dalam memaknai dan menyikapi the others. Tipefikasinya menunjukkan, penyikapan mereka tentang the others cenderung eksklusif, dalam batas-batas tertentu inklusif, sementara tendensi pluralistik cenderung absen. Berdasar itu solusi berupa format ideal pengelolaan keragaman bagi penciptaan koeksistensi antarkelompok keagamaan di Kota Mataram diajukan.